TRANSLATION PROCEDURES USED ON RATU BOKO TOURIST PARK BROCHURE FROM ENGLISH INTO INDONESIAN - Elviran Suriani Dachi; Agnes Nawung; Ni Nyoman Tri Sukarsih (LPPM Universitas Dhyana Pura, 2023)
This study aims to analyze the translation procedure used by the translator in translating the RatuBoko tourist park brochure from English as the source language (SL) to Indonesian as the targetlanguage (TL). Qualitative descriptive method was used in analyzing the data. Data collectiontechniques are carried out by taking notes to collect relevant data from brochures and conducting athorough analysis of the collected data. It includes the seven translation steps proposed by Vinayand Darbelnet (1995), which are divided into two procedures, namely Direct or Literal Translationand Oblique or Free Translation. This analysis process provides an understanding of the strategiesused by translators to communicate messages in brochures accurately and effectively. The focus ofthis research is to analyze data involving the use of seven translation procedures, includingborrowing, calque, literal translation, transposition, modulation, equivalence, and adaptation. Forexample, the word